Livability and futures studies of worn-out urban textures: Scenario analysis for evaluating the livability system and achieving sustainability - Hashemkhani Zolfani, Sarfaraz; Hedayatnezhad Kashi, Seyed Mostafa; Antuchevičienė, Jurgita (International Journal of Strategic Property Management, 2024)
Urban worn-out textures, due to their ancient and historically valuable physical structures, exhibit low adaptability to urban developments and advancements. Tehran, as a city with a rich historical background, also boasts considerable worn-out textures. Due to economic, geographical, and political conditions, a large population resides in these textures. In this regard, the present research aims to investigate the livability status of residents, identify key indicators, and design scenarios in the worn-out textures of Tehran city. This paper proposes a new approach to MicMac that promotes driving forces to scenarios. The results indicate that the livability of residents in worn-out textures of Tehran city, particularly in central regions, is in undesirable conditions. Furthermore, the analysis of the MicMac matrix showed that housing prices, residents’ income, investment, and an increase in economic activities, as well as the role of urban management, are driving forces that have a vital impact on the livability of residents in worn-out textures. These driving forces have depicted three scenarios for the livability of worn-out textures in Tehran city until the year 2032.